Penyajian Laporan Keuangan Sesuai Peraturan Pemerintah No.71 Tahun 2010 tentang Standar Akuntansi Pemerintahan pada Dinas Sosial Provinsisumatera Utara - Ridwan Zulmi; Hendra Harmain (Akuntansi Pajak dan Kebijakan Ekonomi Digital, 2024)
On this occasion, I carried out quite in-depth experiments and research, the aim of which is to observe the preparation of financial reports and the preparation of Government Accounting Standards, namely an accounting method that is implemented when recording and presenting Government Financial Reports. Government Accounting Standards are published and stated in Government Regulation Number 71 of 2010. The Social Service Financial Report contains the mechanism for the Government's Social Service performance in one accounting period. This observation is useful in order to show how the presentation of the financial reports of the North Sumatra Province Social Service is truly in line with Government Regulation Number 71 of 2010. This system uses descriptive analysis which, as a fact, is put together and then classified and managed with special provisions so that it can be picked and described a decision. The results and description of this observation illustrate the presentation of financial reports at the North Sumatra Provincial Social Service in the 2022 budget year with Government Regulation No. 71 of 2010. It is recommended that in the next fiscal year the leadership of the North Sumatra Provincial Social Service illustrate that they have complied with and implemented PP No. 71 of 2010, in this way it can be seen that accountability and transparency of financial reports can be realized.